Assessing climate change causes, risks and opportunities in forestry - Burgess, Paul J.; Moffat, Andy J.; Matthews, Robin B. (Ip Publishing, 2011)
Forests play an important role in regulating the global climate through storing carbon that would otherwise be released as CO 2 to the atmosphere, and affecting the global energy balance through absorption of solar radiation. Forests are also affected directly by the impact of increased CO 2 levels and temperatures on ecosystem processes, and indirectly by human responses seeking to mitigate the net emissions of greenhouse gases (GHGs) or adapt to new climates. This paper attempts to assess the significance of these different aspects, within the context of poverty reduction. It provides a brief assessment of the global role of deforestation on net global GHG emissions; assesses the positive and negative direct effects of climate change on forest productivity, forest disturbance, carbon sequestration, water and air quality, biodiversity and cultural services; and discusses the indirect effects on forestry of human responses to minimise net GHG emissions, through new markets, other land use change, and global, national and local initiatives.
Keywords: forests, climate change, land use change, ecosystem services, biomass, carbon